Differential amplification of Marek's disease CVI988 vaccine and of wild-type isolates from organs of commercial chickens using single or duplexed probes in real-time PCR. Issue 6 (2nd November 2017) - Davidson, Irit; Natour-Altoury, Amira; Raibstein, Israel; Dahan, Yaad
ABSTRACT: The differentiation of Marek's disease virus (MDV)-infected and vaccinated animal (DIVA) test, based on the MDV pp38 gene was described by Baigent et al . [(2016). Real-time PCR for differential quantification of CVI988 vaccine and virulent MDV strains. Journal of Virological Methods, 233, 23-36], using similar primers and alternate probes for virulent MDV-1 and the vaccine CVI988 virus. We explored the assay's applicability for commercial vaccines and commercial chickens, as the above-mentioned study employed tissue-cultured MDV strains and tissues from experimental trials. DNA of visceral organs and feathers of vaccinated or naturally infected chickens was used. Further, the applicability of the DIVA assay was evaluated using single or duplexed probes for the two viruses in the same amplification tube. Due to the high viral content in the commercial vaccines and in the clinical cases of MDV-1 infected commercial chickens, their examination by the MDV-1 DIVA real-time PCR was performed in one step. However, for the feather DNAs of commercially vaccinated birds, a step of pre-amplification was required. The MDV-1 DIVA real-time PCR performed as single probe in separate tubes using the Vir3 probe was very sensitive for virulent MDV-1 strains, but not very specific, as it also gave a clear signal with CVI988 vaccine virus. In contrast, the CVI vaccine probe was specific for CVI988, and did not recognize the MDV-1 strains. When both probes were present in one tube, the CVI probe showed a greater sensitivity for CV1988, while the Vir3 probe showed a much better specificity for virulent MDV-1.